2021
DOI: 10.1097/mph.0000000000002323
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Individualization Using Pharmacokinetic Studies and Joint Ultrasound Imaging in Pediatric Patients With Hemophilia

Abstract: Hemophilia is characterized by bleeding diathesis, primarily affecting the joints. Prophylactic use of missing factor aims at limiting the number of bleeds and, in the long term, the risk of permanent joint damage. However, standard prophylactic regimens are usually applied empirically, not adjusting for variations in bleeding phenotype or drug metabolism. Aim of the present study was to evaluate the need for individualizing prophylaxis, with guidance of pharmacokinetic (PK) studies and joint ultrasound in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The reasons for excluding studies based on full text are summarized in Supplement S2. Eventually, 15 studies 11,12,15,24,29,[38][39][40][41][42][43][44][45][46][47] were included in the systematic review. The 15 included studies reported on occurrence of swelling and synovial proliferation in 2890 joints of 627 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for excluding studies based on full text are summarized in Supplement S2. Eventually, 15 studies 11,12,15,24,29,[38][39][40][41][42][43][44][45][46][47] were included in the systematic review. The 15 included studies reported on occurrence of swelling and synovial proliferation in 2890 joints of 627 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven out of 15 included studies were considered 'screening of index joints' studies 24,29,[38][39][40][41][43][44][45][46][47] and were thus included in a bivariate random-effects model to determine summary estimates for sensitivity and specificity. Subclinical synovial proliferation was found in 4.6-41.7% of the joints in these studies.…”
Section: Meta-analysis Of Screening Studiesmentioning
confidence: 99%